Problematizando a Reforma Psiquiátrica na atualidade: a saúde mental como campo da práxis - Pereira, Erica Cristina [UNESP]; da Costa-Rosa, Abilio [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2012)
Mental Health, in the form of the Psychiatric Reform, and the Anti-Asylum Movement do not ignore the production of knowledge about that field, mainly due to the consolidation of Public Health as a field of knowledge. The article explores some authors who consider Mental Health as a new field of knowledge, introducing a new paradigm in the perception of health - Disease and Care -; however, the goal is to introduce Psychosocial Care as a means to enforce the transdisciplinary and multiprofessional practices. The possibility is that mental health produces developments in Health, consolidating the public policies. In practice, the hospital-centered and drug-based model still predominates, and there are setbacks to be overcome by taking advantage of loopholes capable of breaking with what is instituted.
Questioning the Psychiatric Reform nowadays: mental health as a field of praxis
Keywords: Public Health; Mental Health; Psychosocial Care